2021
DOI: 10.1021/acs.jpcc.1c02456
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Multiple Coordination Numbers in Gold–Cyanoarene Complexes: A Study of the On-Surface Coordination Mechanism

Abstract: In coordination chemistry, knowledge on the oxidation state of the central metal is a significant basis for the design and synthesis of novel complexes. We examined the mechanism of on-surface coordination bonding to d-block metals by investigating the coordination of the newly designed and synthesized 4-(3,3-dimethyl-2,3-dihydro-1H-indol-1-yl)­benzonitrile (IBN) ligand with Au adatoms on a Au(111) surface. The formation of mono-, di-, tri-, and tetra-IBN complexes of gold [Au–(IBN) n (n = 1, 2, 3, and 4)] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Therefore, it is very challenging to identify individual atoms in STM images. As reported in the literature, in some cases, the adatoms in the coordinated complexes can be clearly identified in STM images, however, there are also reports in which the feature for the involved adatoms is invisible. It has been reported that Cu adatoms exist at room temperature, and the density of Cu adatoms on the surface enlarges with the increase of temperature, indicating that Cu adatoms are available for forming complexes in our experiment. In addition, coordination of S atoms to individual Cu is frequently reported, , which also supports our proposed hypothesis.…”
Section: Resultssupporting
confidence: 75%
“…Therefore, it is very challenging to identify individual atoms in STM images. As reported in the literature, in some cases, the adatoms in the coordinated complexes can be clearly identified in STM images, however, there are also reports in which the feature for the involved adatoms is invisible. It has been reported that Cu adatoms exist at room temperature, and the density of Cu adatoms on the surface enlarges with the increase of temperature, indicating that Cu adatoms are available for forming complexes in our experiment. In addition, coordination of S atoms to individual Cu is frequently reported, , which also supports our proposed hypothesis.…”
Section: Resultssupporting
confidence: 75%
“…On the other hand, the distances i 1 = 7.6 Å and i 2 = 10.5 Å between the closest CN and the CH 2 groups estimated for the (8 × 5)-M i 2D layer (230 K, Figures and ) are significantly larger than the typical hydrogen bond lengths reported in the literature. ,, This observation suggests that the other type of surface interactionsthe long-range interactionsmust be responsible for self-assembling in this type of 2D layer.…”
Section: Resultsmentioning
confidence: 74%
“…The attractive interactions within a 2D layer of organic adsorbates are frequently attributed to hydrogen bonding between neighboring species, ,,, which is related to so-called short-range interactions typically acting within 5 Å. The typical length of hydrogen bonds previously reported in the literature amounts to 2.5 ± 0.2 Å as derived from available computational results, 2.9 ± 0.3 Å as directly estimated from the STM results for a variety of organic molecules, ,, and 2.5 ± 0.6 Å as estimated by us from the structural models provided by the authors for various molecules adsorbed on coinage metal surfaces. ,, These values are comparable with the distances between the adjacent CN and CH 2 groups derived from our experimental results for the low-temperature range (169 and 210 K). Specifically, the characterizing distances i 3 = 3.6 Å (cNGs, 210 K) and i 4 = 3.6 Å (hexagons, 160 K) between the CN group of one molecule and the nearest H atom of a neighboring molecule (involved in the terminal CH 2 group) are close to the previously reported typical lengths of hydrogen bonding.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations